ACHIEVING SUSTAINABLE COMPETITIVE ADVANTAGE IN THE METAVERSE: ROLES OF INTELLECTUAL CAPITAL AND SERVICE INNOVATION PERFORMANCE IN HOTELS - Omar ALSETOOHY; Samar SHEIKHELSOUK; Omaima MUNAWAR ALBADRY; Viju MATHEW; Fuad MOHAMMED ALHAMDI; Mahmoud ABOU KAMAR (Geo Journal of Tourism and Geosites)
The concept of the "metaverse" has the potential to fundamentally alter interactions between hotels and individuals within fully connected virtual worlds. This study investigates how Virtual Human Resource Development (VHRD) practices contribute to enhancing Sustainable Competitive Advantage (SCA) in hotels, with consideration of the mediating roles of Intellectual Capital (IC) and Service Innovation Performance (SIP). Data were collected from employees in green hotels in Egypt. Using SmartPLS-SEM, our findings reveal a significant indirect relationship between VHRD and hotel SCA. Furthermore, the study confirms a positive correlation among VHRD, IC, and SIP. Crucially, our results demonstrate that both IC and SIP play positive mediating roles in linking VHRD practices to a hotel's SCA. Hotels should encourage innovative thinking and actions among their employees by integrating virtualized real-life scenarios into HRD practices through IC and SIP to achieve short and long-term SCA objectives.